2015
DOI: 10.1016/j.socscimed.2015.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Tracing shadows: How gendered power relations shape the impacts of maternal death on living children in sub Saharan Africa

Abstract: Driven by the need to better understand the full and intergenerational toll of maternal mortality (MM), a mixed-methods study was conducted in four countries in sub-Saharan Africa to investigate the impacts of maternal death on families and children. The present analysis identifies gender as a fundamental driver not only of maternal, but also child health, through manifestations of gender inequity in household decision making, labor and caregiving, and social norms dictating the status of women. Focus group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
3
9
0
1
Order By: Relevance
“…There was also a significant difference in gender in the multivariable model with females being significantly associated with reporting both parents dead. Some studies have found that girl orphans are more likely to take over household chores in the event of parental death (Chae, 2013; Yamin et al, 2015); however, some girl orphans are also susceptible to early sexual debut and early marriage (Chae, 2013; Yamin et al, 2015). Girls that experience adverse health outcomes from early sexual debut and early marriage, such as HIV, unplanned pregnancy, and other mental health outcomes (Chae, 2013; Yamin et al, 2015), may be more likely to seek services, such as UYDEL, due to these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant difference in gender in the multivariable model with females being significantly associated with reporting both parents dead. Some studies have found that girl orphans are more likely to take over household chores in the event of parental death (Chae, 2013; Yamin et al, 2015); however, some girl orphans are also susceptible to early sexual debut and early marriage (Chae, 2013; Yamin et al, 2015). Girls that experience adverse health outcomes from early sexual debut and early marriage, such as HIV, unplanned pregnancy, and other mental health outcomes (Chae, 2013; Yamin et al, 2015), may be more likely to seek services, such as UYDEL, due to these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Gendered social roles affect the extent to which men get involved in sexual and reproductive health-related matters [7,8]. Gender dynamics also determine the level of autonomy that women have over decisions regarding their health [9]. In majority of communities in sub-Saharan Africa, which are predominantly patriarchal, men are the principal decision-makers, directly or indirectly influencing women's access to and utilization of health services [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Gender inequality has been recognised as an issue in health service delivery, particularly in RMNCH programs in developing countries , but women's significant role in service delivery at the community level, and the gendered nature of human resources for health has been given little priority in research until recently . This reflects historical gender blindness within human resources .…”
Section: Introductionmentioning
confidence: 99%